2018
DOI: 10.1007/s00198-018-4487-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and the risk of osteoporosis among middle-aged and elderly adults: a dose-response meta-analysis

Abstract: It remains unclear how many hours of sleep are associated with the lowest risk of osteoporosis. This meta-analysis was performed to assess the dose-response relationship between sleep duration and risk of osteoporosis. PubMed and Web of Science were searched from inception to December 3, 2017, supplemented by manual searches of the bibliographies of retrieved articles. Data were pooled using fixed- and random-effects models. Restricted cubic spline analysis with four knots was used to model the sleep duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…There was a good correlation between VAS and QUALEFFO-41 in all domains. A similar relationship in women with osteoporosis in Norway was observed by Stanghelle Brita et al [35]. The authors suggest that pain intensity negatively affects HRQoL in women with osteoporosis with or without vertebral fracture [36].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…There was a good correlation between VAS and QUALEFFO-41 in all domains. A similar relationship in women with osteoporosis in Norway was observed by Stanghelle Brita et al [35]. The authors suggest that pain intensity negatively affects HRQoL in women with osteoporosis with or without vertebral fracture [36].…”
Section: Discussionsupporting
confidence: 61%
“…A similar relationship in women with osteoporosis in Norway was observed by Stanghelle Brita et al [35]. The authors suggest that pain intensity negatively affects HRQoL in women with osteoporosis with or without vertebral fracture [36]. Moreover, chronic pain contributes to unbalanced gait, which increases the risk of falls in older people [37].…”
Section: Discussionsupporting
confidence: 54%
“…Human data are limited to mostly cross-sectional studies showing no association [11,12] or that both short [13][14][15][16][17][18][19][20][21][22][23] and long [13][14][15][16][17][24][25][26][27][28][29][30] sleep durations are associated with low BMD (as reviewed in [31]). Of the 20 studies published to date on the association between sleep duration and BMD in humans [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], women comprised the majority of participants. All studies of men used subjective (self-reported) sleep duration and focused primarily on middle-aged adults when it is older men who are at highest risk of bone loss and fracture, and potential effect modifiers, such as vitamin D status, were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep quality has been proven to decrease with age [3], and insufficient sleep and sleep disorder have been associated with adverse outcomes such as weight gain and obesity, diabetes, inflammation, cardiovascular disease, neurocognitive health, mental health and mortality, and these relationships have been widely discussed in the media [4]. It has also been theorised that sleep duration may be associated with risk of osteoporosis, with previous studies suggesting that insufficient or indeed excessive sleep might affect bone health in middle-aged and elderly adults [5]. However, previous studies have focussed mostly on short sleep duration [5][6][7][8][9][10] and obstructive sleep apnoea [11][12][13][14][15][16] as possible contributors to osteoporosis.…”
Section: Introductionmentioning
confidence: 99%